The role of neutrophils in chorioamnionitis - Zhang, Cunling; Cao, Jiasong; Xu, Meiyi; Wu, Dan; Li, Wen; Chang, Ying (Frontiers in Immunology, 2023)
Chorioamnionitis, commonly referred to as intrauterine infection or inflammation, is pathologically defined by neutrophil infiltration and inflammation at the maternal-fetal interface. Chorioamnionitis is the common complication during late pregnancy, which lead to a series of serious consequences, such as preterm labor, preterm premature rupture of the fetal membranes, and fetal inflammatory response syndrome. During infection, a large number of neutrophils migrate to the chorio-decidua in response to chemokines. Although neutrophils, a crucial part of innate immune cells, have strong anti-inflammatory properties, over-activating them can harm the body while also eliminating pathogens. This review concentrated on the latest studies on chorioamnionitis-related consequences as well as the function and malfunction of neutrophils. The release of neutrophil extracellular traps, production of reactive oxygen species, and degranulation from neutrophils during intrauterine infection, as well as their pathological roles in complications related to chorioamnionitis, were discussed in detail, offering fresh perspectives on the treatment of chorioamnionitis.